Exploring self-conscious emotions in individuals with chronic obstructive pulmonary disease: A mixed-methods study. (February 2017) - Harrison, Samantha L; Robertson, Noelle; Goldstein, Roger S; Brooks, Dina
This study aimed to explore the extent to which self-conscious emotions are expressed, to explore any associations with adverse health outcomes, and to compare self-conscious emotions in individuals with chronic obstructive pulmonary disease (COPD) to healthy controls. A two-stage mixed-methods study design was employed. Interviews with 15 individuals with COPD informed the choice of questionnaires to assess self-conscious emotions which were completed by individuals with COPD and healthy controls. Five overarching themes were abstracted: grief, spectrum of blame, concern about the view of others, concealment, and worry about the future. The questionnaires were completed by 70 patients (mean( SD ) age 70.8(9.4) years, forced expiratory volume in one second predicted 40.5(18.8), 44% male) and 61 healthy controls (mean( SD ) age 62.2(12.9) years, 34% male]. Self-conscious emotions were associated with reduced mastery, heightened emotions, and elevated anxiety and depression (all p < 0.001). Individuals with COPD reported lower self-compassion, higher shame, and less pride than healthy controls (all p ≤ 0.01). There is a need to increase awareness of self-conscious emotions in individuals with COPD. Therapies to target such emotions may improve mastery, emotions, and psychological symptoms.